2013
DOI: 10.1155/2013/643927
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Analysis of Semiactive Magnetorheological Dampers Subjected to Harmonic Excitations

Abstract: It has been seen that semiactive magnetorheological (MR) dampers are not sometimes reliable when employed in the building to contract acceleration demand of the stories. In the current paper, a three-storey sample building with semiactive MR dampers subjected to harmonic base excitation is taken under examination to clarify the reliability of such semiactive control systems in mitigation of absolute acceleration response of the buildings. Comparison between semiactively controlled building and uncontrolled ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Future work should include material nonlinearity and other conditions of steel design codes in order to achieve more advanced and direct analysis of frames including tapered members. Also, reliability analysis of tapered mechanical components subjected to harmonic excitations can be accomplished, like Rahbari et al [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Future work should include material nonlinearity and other conditions of steel design codes in order to achieve more advanced and direct analysis of frames including tapered members. Also, reliability analysis of tapered mechanical components subjected to harmonic excitations can be accomplished, like Rahbari et al [16]. …”
Section: Discussionmentioning
confidence: 99%
“…The reliability analysis makes the possibility of estimating the failure probability of the structures with pertinent uncertainties. Some studies in the literature have been conducted on bucklingresistant bracing [1], tuned mass damper [2,3], tuned liquid column dampers [4] viscoelastic dampers [5,6], U-shaped steel dampers [7], magneto-rheological (MR) dampers [8,9], self-centering buckling restrained braces [10].…”
Section: Introductionmentioning
confidence: 99%
“…8). The lateral stiffness coefficients of the superstructure floors from the first floor to the top floor are 514.33, 500.05, 471.47, 428.61, 371.46, 300.03, 214.31, 114.30 kN m −1 , respectively.…”
mentioning
confidence: 99%
“…Results indicated that the design procedure was reliable and the safety of CRSCs is provided; however, the probability failure for mid-rise CRSCs was more than low-rise archetypes. Recently, reliability analysis of different dampers in structures are investigated by simulation methods (Chakraborty and Roy, 2011;Dall'Asta et al, 2017;Rahbari et al, 2013;Xu and Li, 2016). Bagherkhani and Baghlani (2020) assessed the performance and reliability of magnetorheological (MR) fluid dampers in controlling torsional-lateral responses of irregular structures.…”
Section: Introductionmentioning
confidence: 99%